La fine del mondo nel ›De rerum natura‹ di Lucrezio - Galzerano, Manuel (CICERO, 2020)
Lucretius' De rerum natura can be considered as the first Latin "apocalyptic" poem and, at the same time, the most important source on Epicurean cosmic eschatology. This book examines Lucretius' treatment of the mortality of the world, in order to identify the poet's sources and polemical targets and to illustrate his eschatological imagery and rhetoric strategies.